2021
DOI: 10.1002/mgg3.1845
|View full text |Cite
|
Sign up to set email alerts
|

Founder genetic variants of ABCC4 and ABCC11 in the Japanese population are not associated with the development of subacute myelo‐optico‐neuropathy (SMON)

Abstract: SMON research group membersThis is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Comprehensive analyses, including analyses of all SNPs in NQO1, and identification of drug-sensitivity genes are required in future research. This study had limitations similar to those reported previously (Matsumoto et al, 2022). In particular, data for the total dose and duration of clioquinol administration in patients with SMON were lacking.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Comprehensive analyses, including analyses of all SNPs in NQO1, and identification of drug-sensitivity genes are required in future research. This study had limitations similar to those reported previously (Matsumoto et al, 2022). In particular, data for the total dose and duration of clioquinol administration in patients with SMON were lacking.…”
Section: Discussionmentioning
confidence: 64%
“…Both the ABCC4 rs3765534 and the ABCC11 rs17822931 polymorphisms are more common in Japanese people than in Europeans. However, in our previous study, we did not detect an association between the development of SMON and these polymorphisms in the Japanese population (Matsumoto et al., 2022 ).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…It was therefore proposed that a combination of impaired transporter function and transport inhibition by CQ, could trigger SMON pathology, while it could also explain the restriction of SMON to Japan ( Perez et al, 2019 ). However, clinical data suggests that ABCC4 and ABCC11 are not associated with the development of SMON ( Matsumoto et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%